Volume 4: Fluid-Structure Interaction 2015
DOI: 10.1115/pvp2015-45976
|View full text |Cite
|
Sign up to set email alerts
|

Flashing Phenomena of Liquid Nitrogen in a Pressure Vessel Under Rapid Depressurizations

Abstract: In recent years in Japan, the demand of cryogenic fluids like a LH2, LNG is increasing because of the advance of fuel cell device technology, hydrogen of engine, and stream of consciousness for environmental agreement. The purpose of this study is to clarify some fundamental features of the flashing of cryogenic fluids. Experiments on flashing of liquid nitrogen were conducted to clarify the effect of surface roughness of a vessel. Two types of pressure vessel were used. One is a vessel made of stainless steel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Hanaoka [7] conducted blow down experiments for the Freons R-11 and R-113 to clarify the fundamental characteristics of the flashing under slow rate of depressurizations (0.1-2.0MPa/s) and concluded that the correlation of superheated limit of hot water in high depressurization rate examined by Alamgir and Lienhard [8] could not be applied to that of these fluids in low depressurization rate. Furthermore, the authors [9][10][11] conducted flashing experiments of liquid nitrogen from a low temperature technological point of view. These results showed that the pressure undershoots depend significantly on the rate of depressurization and initial temperature even when the depressurization rate is low.…”
Section: Introductionmentioning
confidence: 99%
“…Hanaoka [7] conducted blow down experiments for the Freons R-11 and R-113 to clarify the fundamental characteristics of the flashing under slow rate of depressurizations (0.1-2.0MPa/s) and concluded that the correlation of superheated limit of hot water in high depressurization rate examined by Alamgir and Lienhard [8] could not be applied to that of these fluids in low depressurization rate. Furthermore, the authors [9][10][11] conducted flashing experiments of liquid nitrogen from a low temperature technological point of view. These results showed that the pressure undershoots depend significantly on the rate of depressurization and initial temperature even when the depressurization rate is low.…”
Section: Introductionmentioning
confidence: 99%
“…As the boiling temperatures of cryogenic fluids are very low, various two phase flow phenomena are frequently encountered during their processes such as boiling [1], cavitation [2] and flashing [3]. Occasionally, they might lead to detrimental situations.…”
Section: Introductionmentioning
confidence: 99%